Thermosensitive sex chromosome dosage compensation in ZZ/ZW softshell turtles, Apalone spinifera. (13th September 2021) - Bista, Basanta; Wu, Zhiqiang; Literman, Robert; Valenzuela, Nicole
Abstract : Sex chromosome dosage compensation (SCDC) overcomes gene-dose imbalances that disturb transcriptional networks, as when ZW females or XY males are hemizygous for Z/X genes. Mounting data from non-model organisms reveal diverse SCDC mechanisms, yet their evolution remains obscure, because most informative lineages with variable sex chromosomes are unstudied. Here, we discovered SCDC in turtles and an unprecedented thermosensitive SCDC in eukaryotes. We contrasted RNA-seq expression of Z-genes, their autosomal orthologues, and control autosomal genes in Apalone spinifera (ZZ/ZW) and Chrysemys picta turtles with temperature-dependent sex determination (TSD) (proxy for ancestral expression). This approach disentangled chromosomal context effects on Z-linked and autosomal expression, from lineage effects owing to selection or drift. Embryonic Apalone SCDC is tissue- and age-dependent, regulated gene-by-gene, complete in females via Z-upregulation in both sexes (Type IV) but partial and environmentally plastic via Z-downregulation in males (accentuated at colder temperature), present in female hatchlings and a weakly suggestive in adult liver (Type I). Results indicate that embryonic SCDC evolved with/after sex chromosomes in Apalone 's family Tryonichidae, while co-opting Z-gene upregulation present in the TSD ancestor. Notably, Apalone 's SCDC resembles pygmy snake's, and differs from the full-SCDC of Anolis lizards who share homologous sex chromosomes (XY), advancing our understanding of how XX/XY and ZZ/ZW systems compensate gene-dose imbalance. This article is part of the theme issue 'Challenging the paradigm in sex chromosome evolution: empirical and theoretical insights with a focus on vertebrates (Part II)'.